(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
One of the factors that express the national values and culture of the nation, which show the identity of the nation, is the oral creativity of the people. Proverbs, one of the most important genres of folklore, are one of the most important topics studied in linguistics and folklore. The study and research of proverbs, which are one of the most important genres of folklore, and folk art in general, is of great importance today. This chapter of our scientific work aims to consider universal characteristics of Uzbek and English proverbs and their similarities and differences compared to other genres of folk art. We will also bring up the aspects of the study of Uzbek and English folk proverbs in linguistics and get acquainted with the theories of scientists who worked in this field. Folk proverbs, which arose as a unique phenomenon of language, philosophy and artistic creation, are a genre of folklore with a compact form, but deep content. Each of these artistic drops, which can show the beauty of our language, the elegance of our speech, the intelligence and logic of our thinking with amazing power, are a wonderful mirror of our people’s centuries-old life experiences and everyday life. In this artistic mirror, his attitude to life, nature, man, family and society, socio-political, spiritual-educational, moral-aesthetic and philosophical views, in short, he and his identity are fully manifested. . For this reason, proverbs are very common and have been used for centuries not only in everyday conversation and conversation, but also in artistic, historical and scientific works, political and journalistic literature, and are still very popular today.